Efektivitas Model OPPEMEI untuk Meningkatkan Kemampuan Berpikir Kreatif Mahasiswa - Tri Agustiana, I Gusti Ayu; Agustini, Rudiana; Ibrahim, Musimin; Tika, I Nyoman (Universitas Pendidikan Ganesha, 2020)
The purpose of this research was to improve the students’ creativity and learning outcomes in basic natural science concept course in PGSD Department by using OPPEMEI, it was a new learning model consisted with the steps of learning, such as the orientation, exploration, research, elaboration, exhibition, and implementation. This research used a qualitative descriptive analysis. The subjects of this research were 4 classes (classes F, G, B, and A). Data collection method used creative thinking skills tests with indicators of creative thinking ability which was consisted of fluency, flexibility, elaboration, and originality. Creative thinking skill ability improvement was analyzed by using N-gain. The results showed that there was an improvement in average score of N-gains from the creative thinking skills in the amount of 0.27, 0.153 and 0.101, an improvement occurred in class F. The highest indicator of creative thinking skills was fluency of N-gain in the amount of 0.67. It was categorized into very high criteria. This research showed that the OPPEMEI learning model improved the creative thinking skill ability which would affect the students’ learning outcomes. OPEMEI model would be one of the solutions in the learning process especially in the use of learning models.